Modelling and simulation on temperature and humidity decoupling of indoor environment. (2017) - Yang, Yalong; Wang, Mingyue; Fang, Qiansheng; Wu, Hao; Wu, Wenmiao; Xie, Bao
An air conditioning system plays an important role in regulating the indoor environment and improving the indoor thermal comfort. However, there exists hysteresis of the temperature and humidity regulating system of an air conditioning system. The coupling between temperature and humidity control circuits leads to more energy consumption of the air conditioning system. To solve this issue, an improved feed-forward decoupling model with Smith predictor was designed. The simulation results indicate that it can eliminate the coupling between temperature and humidity regulating circuits. This model can have less time-delay, decoupling between temperature and humidity control circuits. Compared with the conventional method, this decoupling model with Smith predictor has the advantages of timely dynamic response, quick increasing time and less overshoot.